Reduction in aerodynamic drag acting on a commercial vehicle by using a dimpled surface. (2021) - Palanivendhan, M.; Chandradass, J.; Saravanan, C.; Philip, Jennifer; Sharan, R.
Abstract: Advancements in the automotive industry have led to an increasing need to reduce the consumption of fuel, commercial vehicles especially public transport. However, when it comes to commercial vehicles like buses, the reduced mileage stands as a disadvantage. This work proposes a numerical model of a bus (commercial vehicle) with design modifications such as dimples on the surface using the Computational Fluid Dynamics (CFD) to increase the fuel economy. It will help develop the flow structure around the bus to understand the amount of drag. Following the preparation of a generic model of the bus using SOLIDWORKS, the drag coefficient was determined employing a wind tunnel test. The aerodynamic data and the detailed flow structure were studied and analyzed. Accordingly, a modified model was designed, comprising dimpled structures, and the tests repeated. Parameters like dimple position, number of dimples, and dimple orientation were closely observed to understand the performance improvement. It can be an effective method to reduce drag, paving the way to better aerodynamics and increasing fuel economy for such heavy commercial vehicles.